2018
DOI: 10.1186/s12884-018-1861-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cardiovascular hemodynamics in normotensive versus preeclamptic pregnancies: a prospective longitudinal study using a noninvasive cardiac system (NICaS™)

Abstract: BackgroundPreeclampsia is among the most common medical complications of pregnancy. The clinical utility of invasive hemodynamic monitoring in preeclampsia (e.g., Swan-Ganz catheter) is controversial. Thoracic impedance cardiography (TIC) and Doppler echocardiography are noninvasive techniques but they both have important limitations. NICaS™ (NI Medical, PetachTikva, Israel) is a noninvasive cardiac system for determining cardiac output (CO) that utilizes regional impedance cardiography (RIC) by noninvasively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This result was in line with Nikooseresht M et al [10]. Similar to a study done by Lavie A et al [36], in our study, the total estimated blood loss was comparable between groups, and no blood products were required throughout the procedure.…”
Section: Vs1653 Ml±331)supporting
confidence: 93%
See 1 more Smart Citation
“…This result was in line with Nikooseresht M et al [10]. Similar to a study done by Lavie A et al [36], in our study, the total estimated blood loss was comparable between groups, and no blood products were required throughout the procedure.…”
Section: Vs1653 Ml±331)supporting
confidence: 93%
“…Preeclampsia with severity feature/severe preeclampsia: Defined as a systolic arterial blood pressure of 160 mmHg or higher, or a diastolic blood pressure of 110 mmHg or higher, associated with proteinuria > 5 g in 24 hours [10,35]. Change in heart rate: When there was a 20% decrease or increase in heart rate from baseline [6,10,25,26,36]. The magnitude of hemodynamics change/severity of hypotension: The percentage falls of blood pressure (SBP, DBP, and MAP) between two measurements and it was calculated as:…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies investigating CO during delivery using a modified pulse‐pressure method after arterial and central venous catheterization and continuous‐wave ultrasound have suggested that SV and CO increase during labor and immediately postpartum owing to pain, maternal bearing‐down efforts and the increase in venous return by autotransfusion from the contracted uterus and the sudden release of inferior vena cava obstruction. This has been accepted as common knowledge for several decades, but recent prospective studies using continuous measurements suggest a different perspective, with similar baseline hemodynamic parameters during the course of labor (stages 1 and 2 and postpartum) and substantial hemodynamic stress during contractions, without an increase in CO immediately postpartum.…”
Section: Physiology In Pregnancymentioning
confidence: 99%
“…However, spinal anesthesia-induced maternal hypotension is still the most frequent complication [16,17]. Anesthetists denied spinal anesthesia for preeclamptic parturients, due to the fear of profound hypotension and its management crisis (exaggerated response to vasopressor treatment and pulmonary edema following fluid challenges) [9,13,[18][19][20]. Furthermore, the incidence of spinal anesthesia-induced maternal hypotension showed inconsistency across different studies, which makes it almost difficult to set standard targets and develop a local management protocol [16,17,21].…”
Section: Introductionmentioning
confidence: 99%